Advances in imaging and electron physics. (Advances in imaging and electron physics ;, 2023)
The series features articles on the physics of electron devices (especially semiconductor devices), particle optics at high and low energies, microlithography, image science, digital image processing, electromagnetic wave propagation, electron microscopy and the computing methods used in all these domains.